The Effect of Self-Efficacy and Self-Esteem on Academic Achievement of Grade 10 Students at MAN Kota Palangkaraya - Fahrurrazi Fahrurrazi; Asep Solikin; Agung Riadin (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Academic performance among adolescents in Palangkaraya City is influenced by various internal factors, specifically the psychological constructs of self-efficacy and self-esteem. This study aims to investigate the relationship between self-efficacy, self-esteem, and the academic achievement of students. The research utilizes a quantitative approach with a correlational study design. The sample consists of 183 students from MAN Palangkaraya, selected to represent the student population in the region. Data were collected using Indonesian-adapted versions of the Academy Self-efficacy Scale and the Self-esteem Inventory – Long Form (SEI-LR). To ensure the instruments' cultural and linguistic suitability, a pilot study was conducted to establish reliability and validity within the local context. A Pearson correlation analysis will be conducted to evaluate the linear relationship between these variables. It is hoped that the findings will contribute to a deeper understanding of how self-efficacy and self-esteem impact academic success. The results are intended to provide a guide for developing educational strategies focused on enhancing these psychological traits to improve overall student academic achievements.